DC Brushless Motor Control Design and Preliminary Testing for Independent 4-Wheel Drive Rev-11 Robotic Platform - Saputra, Roni Permana; Ardiansyah, Rizqi Andry; Mirdanies, Midriem; Santoso, Arif; Nugraha, Aditya Sukma; Muqorobin, Anwar; Saputra, Hendri Maja; Susanti, Vita; Rijanto, Estiko (Journal of Mechatronics, Electrical Power and Vehicular Technology, 2011)
This paper discusses the design of control system for brushless DC motor using microcontroller ATMega 16 that will be applied to an independent 4-wheel drive Mobile Robot LIPI version 2 (REV-11). The control system consists of two parts which are brushless DC motor control module and supervisory control module that coordinates the desired command to the motor control module. To control the REV-11 platform, supervisory control transmit the reference data of speed and direction of motor to control the speed and direction of each actuator on the platform REV-11. From the test results it is concluded that the designed control system work properly to coordinate and control the speed and direction of motion of the actuator motor REV-11 platform.Â